2017
DOI: 10.15406/mojph.2017.06.00161
|View full text |Cite
|
Sign up to set email alerts
|

Women Autonomy and the Use of Antenatal and Delivery Services in Nigeria

Abstract: The ability of a woman to make independent decision and appropriate action on her reproductive desires is dependent on her level of autonomy. This study was undertaken to determine whether the level of autonomy of Nigerian women influences the use of antenatal and delivery services. A quantitative cross-sectional study using the Demographic and Health Survey (DHS) to determine whether an association exists between women's autonomy and the appropriate use of prenatal and delivery services. A total of 22,556 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
1
2
0
1
Order By: Relevance
“…This may be due to the fact that using their autonomy women can make decisions about getting healthcare for themselves. Similar studies also showed similar finding [39,[53][54][55].…”
Section: Discussionsupporting
confidence: 82%
“…This may be due to the fact that using their autonomy women can make decisions about getting healthcare for themselves. Similar studies also showed similar finding [39,[53][54][55].…”
Section: Discussionsupporting
confidence: 82%
“…Research on patient-centered care for women shows that women’s autonomy (i.e., the freedom of women to exercise their judgment in order to act for their own interests) influences reproductive, maternal, and child health outcomes [ 6 11 ]. Conversely, the absence of women’s autonomy in decision-making results in delays and poor utilization of maternal health services and ultimately increased maternal morbidity and mortality [ 12 ]. Thus, empowered women can make informed decisions about their reproductive health, including family planning, timing and spacing of pregnancies, and the type of care they receive during pregnancy and childbirth [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on patient-centered care for women shows that women's autonomy (i.e., the freedom of women to exercise their judgment in order to act for their own interests) in uences reproductive, maternal, and child health outcomes (6)(7)(8)(9)(10)(11). Conversely, the absence of women's autonomy in decision-making results in delays and poor utilization of maternal health services and ultimately increased maternal morbidity and mortality (12). Thus, empowered women have the ability to make informed decisions about their reproductive health, including family planning, timing and spacing of pregnancies, and the type of care they receive during pregnancy and childbirth (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%